(untitled) (Quaestiones Disputatae: temas en debate, 2018)
When analyzing conversational spontaneous issues like, classroom interaction, IRF cycle, teacher talk, overlapping, and adjacency pairs inside a virtual environment in a Colombian public technical institution, we found that these aspects support the pedagogic purpose of the class and at the same time, they display the teacher and students’ identity while performing a foreign language lesson. The participants of the analysis were an English teacher and his 6 students in a computer mediated-environment with a double way interaction tool (a chat bar and an audio interchange program). The ﬁndings from this discourse analysis between the teacher and students’ interaction revealed that the virtual environment has some common dynamics to the face to face setting and that managerial mode has an outstanding place in this kind of classroom.